PENENTUAN CT DOSE INDEX (CTDI) UNTUK VARIASI SLICE THICKNESS DENGAN PROGRAM DOSXYZNRC - Andriani, Intan; Anam, Choirul; Setiawati, Evi (BERKALA FISIKA, 2012)
The calculation of CT dose and CTDI has been done by using DOSXYZnrc software. TwoÂ kinds of phantoms have been used, i.e air and PMMA phantoms. The volume of phantoms 16 x 16x 16 cm3. The simulation carried out at 120 kV and the particles source 106. The calculation ofdose at the mid of phantom at the z axis, every voxel 0,2 x 0,2 x 0.2 mm3. The Â variation of slicethickness were 5 mm, 10 mm, 15 mm and 20 mm. The dosages at every point then were plotted tofind out dose profile, and then were integrated to find out the CTDI. It was obtained that the peakvalue Â on the air phantom has a higher value than the PMMA phantom. In the air phantom at theslice thickness of 5 mm, 10 mm, 15 mm and 20 mm were 68.28%, 80.49%, 90.91%, 99.86%. Whilein PMMA were 63.68%, 77.42%, 89.32%, 100%. At the penumbral region, it was obtained thatdosage at the PMAA phantom has a higher than the air phantom. CTDI from the PMAA phantomwas 212.50% and the air phantom was 184%. It was obtained that CTDI independent of slicethickness at the range 5-20 cm.Keywords: DOSXYZnrc, Slice thickness, CTDI